2009
DOI: 10.1007/s00595-008-3861-0
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative enteral nutrition is useful for recovering gastrointestinal motility and maintaining the nutritional status

Abstract: Enteral nutrition should therefore be initiated soon after surgery if the gastrointestinal tract is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…[28][29][30][31][32] Uncomplicated GDV cases will usually resume voluntary food consumption within 1-3 days postoperatively. In complicated cases, nutritional support in the form of nasogastric or nasoesophageal tube feeding or peripheral or central parenteral nutrition is necessary.…”
Section: Management Of Gastrointestinal Dysfunctionmentioning
confidence: 99%
“…[28][29][30][31][32] Uncomplicated GDV cases will usually resume voluntary food consumption within 1-3 days postoperatively. In complicated cases, nutritional support in the form of nasogastric or nasoesophageal tube feeding or peripheral or central parenteral nutrition is necessary.…”
Section: Management Of Gastrointestinal Dysfunctionmentioning
confidence: 99%
“…In a recent study evaluating the effect of enteral versus parenteral nutrition on motility, Kawasaki et al [22] recorded gastrointestinal motility up to postoperative day 8 after partial resection of the rectum ICU interventions on intestinal motility Fruhwald and Kainz 161 in beagle dogs receiving enteral (n ¼ 6) or parenteral nutrition (n ¼ 6). The migrating motor complex (fasting motility) was absent in both groups on postoperative day 1, reappeared in the enteral nutrition group on day 2 and was normal on day 4, whereas in the parenteral nutrition group, only 50% of the dogs had normal fasting motility [22]. Moore-Olufemi et al [23] demonstrated that early enteral nutrition improves intestinal transit in rats.…”
Section: Enteral Nutrition and Gastrointestinal Functionmentioning
confidence: 98%
“…In a canine model, Kawasaki and colleagues [37] compared the effects of enteral nutrition on GI motility after open abdominal surgery. They demonstrated that enteral nutrition hastened recovery of gut motility.…”
Section: Traditions and Dogmasmentioning
confidence: 99%